Structure and characterization of the ribosomal transcription units of small liver flukes, Opisthorchis viverrini, O. Felineus and Clonorchis sinensis - Thanh Hoa, Le; Thi Bich Nga, Nguyen; Thi Thanh Huong, Doan; Kim Xuyen, Le Thi; Thi Khue, Nguyen (Vietnam Journal of Biotechnology, 2020)
Opisthorchiasis is a zoonotic parasitic infection caused by small liver fluke species, Opisthorchis viverrini, O. felineus and Clonorchis sinensis, in the family Opisthorchiidae. Vietnam has both species, of which C. sinensis is distributed in the northern and O. viverrini in the central provinces. In addition to the mitochondrial genomes, the ribosomal DNA sequences (rDNA) of these species are highly needed to obtain for providing molecular markers in species identification, classification, phylogeny and evolutionary studies. In this study, the near/complete nucleotide sequences of ribosomal transcription units (rTU) from O. viverrini (Vietnamese sample), O. felineus (Russian sample) and C. sinensis (Vietnamese sample) were analyzed. All rTUs for three species were determined, which is 7,839 bp for O. viverrini, 6,948 bp for O. felineus and 7,296 bp for C. sinensis containing structures of 18S, ITS1, 5,8S, ITS2 and 28S. The IGS region was not obtained for all three species. In all three species, sequence analysis revealed 2 tandem repetitive elements of 47-48 bp/each in ITS1 but not in ITS2. The nucleotide sequences of 18S, ITS1, ITS2 and 28S are valuable ribosomal markers that this study provides for diagnosis, identification, taxonomic classification and population genetics. In conclusion, the rTU sequences for the three species of the family Opisthorchiidae have been identified and provides molecular markers for the use of phylogenetic analysis for species/family classification in the superfamily Opisthorchioidea and the class Trematoda.